(3GdeLdO (B1 (3GdMjGI GdOhdjI GdbGfhf GdOHdheGSj hGdbGfhf GdbfUdj hGdbGfhf GdOhdj ddHMQs - (3eMeO SGej(B, (3YHO GdMejOs ((3GdEScfOQjI(B:s (3OGQ GdeWHhYGJ GdLGeYjI(B,s, 1998)
(3GdbGfhf GdOHdheGSj hGdbGfhf GdbfUdj, GdbGfhf GdOHdheGSj, GdJeKjd GdOHdheGSj, GdeNJUhf HJeKjd GdOhdI, GdYdGbGJ GdOHdheGSjI, GdMUGfGJ hGdGeJjGRGJ GdOHdheGSjI, GdbGfhf GdbfUdj, GdbGfhf GdOhdj ddHMQ hbGfhfg, aj GdJYQja HGdSajfI hHjGf WHjYJgG GdbGfhfjI hCfhGYgG, CbSGe GdHMQ hefGWbg, GdGbdje GdHMQj ddOhdI, GdejGg GdHMQjI ddOhdI, GdHMQ GdYGdj, GdeeQGJ GdHMQjI GdOhdjIs
Keywords: (3GdbGfhf GdOhdjs; (3Gdfbd GdHMQjs